Development and optimization of multivesicular gefitinib liposomal transdermal system employing lipoid S100 for breast cancer: pharmacokinetics, bioavailability, and skin irritation studies in Wistar rats - Jyoti S. Patel; Nulgumnalli Manjunathaiah Raghavendra; B. Sajeev Kumar (SpringerOpen, 2024)
Abstract Background Conventional therapies in cancer treatment face challenges including drug resistance, lack of specificity, and severe adverse reactions. This study explores the potential of liposomal transdermal delivery systems as an alternative to current therapies with improved BA and PK. The objective of the study was to formulate gefitinib liposomes by thin film hydration technique (TFH) using lipoid S100. A central composite design (CCD) was used to develop and optimize GEF-LIP-TDDs and to analyze the optimum concentrations of the selected variables (phospholipid, cholesterol) in liposomal formation. The model fitting was performed using Design-Expert (Stat-Ease, Ver 13). The GEF liposomes were evaluated for %EE, mean particle size and PDI. The optimized liposomes were fabricated as a transdermal patch by mercury substrate method and evaluated for %drug content, in vitro diffusion, in vivo biodistribution (PK and BA), and skin irritation studies in female Albino Wistar rats. The stability of the optimized transdermal patch was also assessed for 3 months. Results The CCD model was significant with F-value of 37.97, P-value of 0.0500 and R 2 of 0.9644. The average vesicle size, PDI, and ZP of GEF-LIPs (F1-F13) were found to be between 112.8 to 373.7 nm, 0.186 to 0.510 and − 3.69 to − 82.2 mV, respectively. F3-GEF-LIP exhibited a mean vesicle size of 96.07 nm, ZP of − 46.06 mV, and a PDI of 0.423. F3-GEF-LIP demonstrated exceptional %EE (97.79) and sustained release effect (%CDR, 83.32) following a diffusion-controlled mechanism. TEM images confirmed liposomes of multivesicular type (MVV, < 100 nm). Importantly, optimized F3-GEF-LIP-TD showed no signs of edema in Wistar rats. The biodistribution of F3-GEF-LIP-TD was similar to pure GEF and was higher in the liver (p < 0.05). The BA of F3-GEF-LIP-TD was observed to be 74.05 ± 0.11% in comparison with oral GEF-LIP (65.25 ± 0.08%) and pure GEF (58.10 ± 0.17%). Conclusion TFH technique offers stable liposomes with high reproducibility. Our findings imply that GEF-LIP-TD provides enhanced BA and tissue distribution and can be considered as a substitution for orals or in combination for treating breast cancer. Lipoid S100 is a potential lipid for developing stable multivesicular nanoliposomes. Graphical abstract